Analysis of SARS-CoV-2 spike-Induced Syncytia with Lifeact-GFP as Biosensor Using High-Content Screening Instrument for Automated Syncytia Counting - Fauziah, Dita; Septisetyani, Endah Puji; Yerizel, Eti; Kastian, Ria Fajarwati (Indonesian Journal of Cancer Chemoprevention, 2024)
SARS-CoV-2 is believed to cause cytopathic effects in forming multinucleated cells, known as syncytia. Syncytia due to SARS-CoV-2 infection found in lung tissue samples of COVID-19 patients represents a case of COVID-19 with a poor prognosis. Therefore, it is very important to study the mechanism of syncytia formation and to test candidate materials that can inhibit the occurrence of syncytia and potentially be applied in the treatment or prevention of COVID-19. Since syncytia counting and analysis are time-consuming, we utilized a high-content screening (HCS) instrument in this study to automate syncytia analysis. We used 293T cells transfected with plasmids to express the SARS-CoV-2 spike, human angiotensin-converting enzyme-2 (hACE-2), and a plasmid encoding lifeact-GFP as an F-actin biosensor to facilitate syncytia analysis using the HCS instrument. In this study, syncytia analysis was carried out using HCS software. The HCS application categorizes cells as multi-nuclei by counting the number of cell nuclei stained with DAPI in cells that emitted green fluorescence due to lifeact-GFP expression. Syncytia analysis is time-consuming because of the calculation of the number of syncytia formed in a confluent cell monolayer culture. Hopefully, utilizing the HCS platform can accelerate the test of syncytia inhibition after various treatments using test compounds.Keywords: 293T cells, high-content analysis, SARS-CoV-2, spike, syncytia.